Changing clinical expression of Behçet disease in Korea during three decades (1983–2012): chronological analysis of 3674 hospital‐based patients. (18th February 2014) - Kim, D.Y.; Choi, M.J.; Cho, S.; Kim, D.W.; Bang, D.
Abstract : What's already known about this topic? Recent reports suggest that the clinical manifestations of Behçet disease (BD), a chronic multisystemic vasculitis, are lessening. What does this study add? During the past three decades in Korea, rates of BD in male patients, and complete type disease have proportionately declined, and patterns of organ involvement have shifted. Many factors, including heightened personal hygiene, technical advances and various medications, may modify the clinical features of BD. Summary: Background: Behçet disease (BD) is a chronic multisystemic vasculitis affecting blood vessels of any calibre or type. Recent evidence suggests that the clinical expression of BD is lessening. Objectives: To examine the clinical expression of BD in Korea during the past three decades via a large patient registry. Methods: Initial manifestations of patients with BD seen at a tertiary referral hospital between 1983 and 2012 were reviewed retrospectively, stratifying patients by decade to compare epidemiological data and cardinal symptoms. Results: In total 3674 patients with BD were reviewed. Significant proportional declines occurred with respect to male sex, complete type BD and major presenting features (genital ulcers, ocular involvement and skin lesions), whereas the mean patient age rose progressively, as did the frequencies of joint, gastrointestinal and central nervous system manifestations (all P < 0·0001). Conclusions: During the past three decades, clinical expression of BD in Korea has changed, resulting in fewer instances of complete type disease, declining male propensity, and shifting patterns of organ involvement.